Reduced Expression of Gongdae Ring Zinc Finger 1(GdRZF1) Enhances Drought Stress Tolerance in Watermelon (Citrullus lanatus) - Chung, Jung-Sung; Park, Seung-Hyeon; Min, Ji-Hee; Min, Kwang-Hyun; Lee, Sungbeom; Lee, Kyeong-Hwan; Kim, Cheol Soo (Weon'ye gwahag gi'sulji, 2017)
Watermelon is a major fruit vegetable around the world. Drought is an abiotic stress factor thataffects the productivity and growth of crop plants. To improve the tolerance of watermelonto drought stress, it is important to isolate stress tolerance-related genes. Recently, wecharacterized the gene for a ubiquitin E3 ligase protein named Lagenaria siceraria RING ZincFinger 1 (LsRZF1) . In Arabidopsis , LsRZF1 is involved in the drought response throughthe proline metabolism-mediated pathway. In this study, we identified and characterizeda watermelon (Citrullus lanatus cv. Gongdae) homolog of LsRZF1 , designated GdRZF1. LsRZF1 antisense (lsrzf1 ) transgenic watermelon lines showed reduced GdRZF1 expression,and were less sensitive to drought stress than the wild type. Reduced expression of GdRZF1was also significantly influential in changes in drought-sensitive parameters including relativewater content, ion leakage, chlorophyll content, malondialdehyde levels, proline content, andthe expression of drought stress-associated genes. Taken together, these findings suggest thatGdRZF1 is important for water deficit tolerance in watermelon KCI Citation Count: 0